Diversity of Soil Nematode in Utilization Block Integrated Educational Conservation Forest, Wan Abdul Rachman Great Forest Park - Yoshua Gdemakarti Panjerrino; Bainah Sari Dewi; I Gede Swibawa (Jurnal Sylva Lestari, 2019)
Change of land forest in Wan Abdul Rachman Forest Park became agroforestry, affect of cover condition and decrease the content of soil matter. Nematode was one of the soils biotas that can be used as an indicator of change in the soil status. The aim of study is to know the community and diversity of nematodes on the Utilization Block, Integrated Educational Conservation Forest, Wan Abdul Rachman Great Forest Park. The research was conducted in April to May 2018. The soil samples were taken on arboretum one, arboretum two, arboretum three and arboretum four in Integrated Educational Conservation Forest, Wan Abdul Rachman Great Forest Park. Nematode observations were conducted in the Plant Pests Laboratory, Faculty of Agriculture, University of Lampung. Nematodes was identified to genus level based on morphological traits. The analysis used were including the index of diversity, dominance and similarities between genus arboretum. The results showed that there were 30 genus of nematode consists of 19 plant parasitic nematode genera, six nematoda bacterial-feeding, three nematode fungal-feeding and two predator nematodes. The dominant nematode genera were Criconomella, Helycotylenchulus and Rotylenchulus. The abundance of nematodes ranges from 171-617 individuals/300cm3 soil. The diversity of soil nematodes based on the Shannon-Wienner index ranges from 2,47 – 2,80. The Shannon-Whienner Index criteria were classified as moderate. The Simpson Index ranges from 0,89 – 0,93. The highest similarity index genus in arboretum three and four with a value of 0,81 and the lowest in arboretum two and three which is 0,54.